PENGARUH PEMBINAAN OLEH KEPALA SEKOLAH, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN SAPURAN KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine the influence of coaching by the principal, motivation, and work environment on the performance of teachers in the District Junior High School Sapuran Wonosobo regency. And what is the most influential variable on teacher performance among these three variables.The population were Junior High School teacher in the district, amounting to 5 Sapuran SMP with the number of teachers by 80 people and research is the study population. Data were collected using a questionnaire / direct questionnaires answered by teachers, from 80 questionnaires / questionnaires were distributed back 71 or 89%. The questionnaire data were analyzed with the statistical technique of multiple regression analysis and partial correlation analysis using SPSS.The results showed that simultaneous guidance by the principal, motivation and work environment affect the performance of the teacher with the contribution of these three factors influence the effectiveness of 64.61% and 35.39% influenced by other factors (unexplained factors). The results of the analysis of coaching by the principal influence on the performance of teachers to influence the effectiveness of the contribution of 26.31%. The results of the analysis on the performance of teacher motivation to influence the effectiveness of the contribution of 22.84%. The results of the analysis of the work environment affects the performance of teachers and influence the effectiveness of the contribution of 15.46%.Thus shows that when coaching by the school principal, motivation, and work environment increases, the performance of teachers will also increase.